2020
DOI: 10.1111/jfpp.14995
|View full text |Cite
|
Sign up to set email alerts
|

Extraction optimization and microencapsulation of phenolic antioxidant compounds from lemon balm ( Melissa officinalis  L.): Instant soluble tea production

Abstract: The purpose of this study was to extract phenolics from lemon balm followed by microencapsulation with spray drying. The optimum extraction conditions were 100°C for the temperature and 120 min for the time with TPC of 6,365 mg GAE/100 g and ABTS radical scavenging activity of 9,196 mg TEAC/100 g. Lemon balm extracts were spray dried using three different air inlet temperatures (130°C, 165°C, and 200°C) of which 165°C was provided better scores than the other points in terms of microencapsulation yield (65.9%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
1
10
0
3
Order By: Relevance
“…Although extraction condition studies have been reported by many researchers, the evaluation of the instant tea powders of Lithocarpus litseifolius [Hance] Chun is very limited. In our study, the yield of the instant sweet tea powder increased with the extraction temperature from 55 to 85 • C, and this result was similar to other studies [14,24], suggesting that a higher yield of instant tea powder might be associated with a higher phenolic content. As the temperature increases, the plant tissue softens and the viscosity and surface tension of water decrease, resulting in the dissolution of more phenolic compounds [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although extraction condition studies have been reported by many researchers, the evaluation of the instant tea powders of Lithocarpus litseifolius [Hance] Chun is very limited. In our study, the yield of the instant sweet tea powder increased with the extraction temperature from 55 to 85 • C, and this result was similar to other studies [14,24], suggesting that a higher yield of instant tea powder might be associated with a higher phenolic content. As the temperature increases, the plant tissue softens and the viscosity and surface tension of water decrease, resulting in the dissolution of more phenolic compounds [25].…”
Section: Discussionsupporting
confidence: 91%
“…However, other researchers found that instant black teas prepared by fermented dhools showed higher polyphenolic and theaflavin contents, as well as antioxidant activities than those prepared by black tea and BMF [8]. In addition, the extraction/brew conditions (e.g., extraction temperature and time, brewing time, and water volume) were found to significantly influence the total soluble solid, phenolic content, and antioxidant activity of instant teas [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the water extraction conditions resulted in 100 °C for 120 min as the optimum conditions for TPC recovery and antiradical (DPPH, ABTS + ) activity of the extracts [ 138 ]. Hydrolysis with 0.2 M hydrochloric acid increased the TPC content of the extract, and the FRAP, indicating that glycosylated forms might have been hydrolyzed to the respective aglycons that present higher antioxidant power.…”
Section: Lemon Balmmentioning
confidence: 99%
“…Additionally, they proved effective antioxidants for lipid protection in oils and emulsions [ 112 ]. Water extracts, rich in phenolic compounds were effectively encapsulated in maltodextrin, by spray drying [ 138 ]. However, there is a need for further study towards the purification and formulation of these extracts in order to be exploited commercially.…”
Section: Lemon Balmmentioning
confidence: 99%
“…In this study, sunflower oil has been selected as the case model, since it is the most used oil in European countries for frying foods and margarine production as well as salad dressing (Yanishlieva & Marinova, 2001). On the other hand, lemon balm ( Melissa officinalis ) has been reported to have antioxidant properties due to its phenolic substances (Dastmalchi et al, 2008; Kamdem et al, 2013; Miron et al, 2013; Tülek et al, 2021). Therefore, it was used as an natural antioxidant to increase the oil's resistance to oxidation.…”
Section: Introductionmentioning
confidence: 99%